Henry IV of France as he lay in state after his murder in the year... - Robert Dunkarton /... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Henry IV of France as he lay in state after his murder in the year 1610, engraving after Quesnel - Gallica 2010. Caption: "The most high puissant and excellent Prince Henry the Great, King of France, and Navarre, &c. &c. as he lay in state after his murder, anNo 1610. Engraved by R. Dunkarton from a rare print engraved by J. Briot, after Quesnel. London: Published by S. Woodburn, 112 St. Martin's Lane. Proof"
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons